The richest poor kid - Sommer, Carl, 1930-; Martinez, Jorge, 1951- (Houston : Advance Pub., 2007)
Randy hates being poor, so when he is magically granted two wishes, the first thing he wishes is for everything he touches to turn to gold.
Keywords: Family life -- Fiction; Wishes -- Fiction; Gold -- Fiction